Finger-like patterns in sedimenting water-sand suspensions - Schröter, Matthias; Engel, Andreas; Rehberg, Ingo; Lange, Adrian; Betat, André; Iori, Giulia; Völtz, Camilla (Physics Reports-Review Section of Physics Letters, 2000)
The temporal evolution of a water-sand interface driven by gravity is experimentally investigated. By means of a Fourier analysis of the evolving interface the growth rates are determined for the different modes appearing in the developing front. To model the observed behavior we apply the idea of the Rayleigh-Taylor instability for two stratified fluids. Carrying out a linear stability analysis we calculate the growth rates from the corresponding dispersion relations for finite and infinite cell sizes and compose those results with the experimental data. Alternatively, the situation of the sedimenting sand can be modeled by a two-dimensional cellular automaton. A qualitative similarity between that model and the experimental situation is obtained. © 2000 Elsevier Science B.V.
Keywords: 05.45. - a